MIXED METHOD ANALYSIS IN ASSESSING THE EFFECTIVENESS OF INTENTIONAL LEARNING INSTRUMENTS IN TEACHING CIRCUITS - Bucayong, Cecilia O (PEOPLE: International Journal of Social Sciences, 2019)
Research results on Intentional Learning proved positive implications in the teaching and learning processes. In this study, the researcher analyzed data gathered from the implementation of Intentional Learning Questionnaire in Electric Circuit (ILQ-EC) and Intentional Learning Module (ILM) as the intentional learning instruments. The over-all study involves implementation of ILQ-EC, development of ILM and testing its effectiveness using quantitative and qualitative research analysis. Previous research used ILQ-EC in identifying motivation and learning strategies factors which were highly correlated and predictive to conceptual understanding of student respondents. These factors served as the benchmark in the development and testing of ILM for this present study. Results for both quantitative and qualitative analysis showed that high gainers tend to be more intentional, specifically, more critical thinker and with higher perceived competence than low gainers. Moreover, average normal gains of the student-participants after using ILM was higher compared to previous research results using different learning approaches. ILM evaluation based on student responses also confirmed the influence of ILM in their learning gains. Thus, enhancing intentionality proved significant effect in the teaching and learning process.